The Key Role of Ambulatory Blood Pressure Monitoring in the Detection of Masked Hypertension and Other Phenomena in Frail Geriatric Patients - Koudelka, Marek; Sovová, Eliška (Medicina (Kaunas, Lithuania), 2021)
Background and Objectives: This study aims to determine prevalence of masked uncontrolled hypertension (MUH) in frail geriatric patients with arterial hypertension and thus show the role of ambulatory blood pressure monitoring (ABPM) since hypertension occurs in more than 80% of people 60+ years and cardiovascular diseases are the main cause of death worldwide. Despite modern pharmacotherapy, use of combination therapy and normal office blood pressure (BP), patients' prognoses might worsen due to inadequate therapy (never-detected MUH). Materials and Methods: 118 frail geriatric patients (84.2 ± 4.4 years) treated for arterial hypertension with office BP < 140/90 mmHg participated in the study. 24-h ABPM and clinical examination were performed. Results: Although patients were normotensive in the office, 24-h measurements showed that BP values in 72% of hypertensives were not in the target range: MUH was identified in 47 (40%) patients during 24 h, in 48 (41%) patients during daytime and nocturnal hypertension in 60 (51%) patients. Conclusions: ABPM is essential for frail geriatric patients due to high prevalence of MUH, which cannot be detected based on office BP measurements. ABPM also helps to detect exaggerated morning surge, isolated systolic hypertension, dipping/non-dipping, and set and properly manage adequate treatment, which reduces incidence of cardiovascular events and contributes to decreasing the financial burden of society.
Keywords: křehký senior; Humans; Risk Factors; Hypertension; Masked Hypertension; rizikové faktory; Aged; senioři; lidé; Blood Pressure Monitoring, Ambulatory; ambulantní monitorování krevního tlaku; frailty; masked hypertension; krevní tlak; hypertenze; masked uncontrolled hypertension; maskovaná hypertenze; Frail Elderly; ambulatory blood pressure monitoring (ABMP); Blood Pressure; geriatric patient